The Effect of Workload and Work Environment on the Performance of Injection Department Employees: A Case Study of PT. Hijau Elektronika Indonesia - Ida Darmilah; Istianah Setyaningsih (ProBisnis : Jurnal Manajemen, 2025)
Employee performance is one of the key factors in achieving company objectives. However, performance is often influenced by various factors, including workload and work environment. Excessive or insufficient workload can reduce productivity, while an unconducive work environment may hinder comfort and work effectiveness. This study aims to determine the effect of workload and work environment on the performance of Injection section employees at PT Hijau Elektronika Indonesia. This research employed a quantitative method with a survey approach. The population consisted of all 114 female employees in the Injection section, with the sampling technique using a saturated sampling method. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, F-test, t-test, and the coefficient of determination (R²) with the assistance of SPSS version 20. The results showed that workload had a positive and significant effect on employee performance (sig. 0.004 < 0.05), work environment had a positive and significant effect on employee performance (sig. 0.000 < 0.05), and both variables simultaneously had a positive and significant effect on employee performance (sig. 0.000 < 0.05). The R² value of 0.447 indicates that 44.7% of the variation in employee performance is explained by workload and work environment, while the remaining 55.3% is influenced by other factors. Based on these findings, the company is advised to manage workload proportionally and create a safe, comfortable, and supportive work environment, considering that the work environment is the most dominant variable affecting employee performance.